Europe and South-East Asia: Shifting from diplomacy to unilateralism - Hanna Deringer; Hosuk Lee-Makiyama; Danny Murty (European Centre for International Political Economy (ECIPE), 2019)
The postponement of the planned "strategic partnership" between the Association of Southeast Asian Nations (ASEAN) and the EU highlights deep concerns and divisions for opening up in the relationship. The EU-Singapore Free Trade Agreement (FTA), and Investment Partnership Agreement (IPA), stand alone as a success for EU-ASEAN trade relations, in an otherwise troubled landscape. Bilateral trade agreements with Vietnam, Malaysia, Indonesia and Thailand remain frozen or unratified for multiple non-trade reasons, often stemming from domestic politics. The treatment of palm oil remains a substantial impediment to improving relations. The EU's delegated regulation, an addition to the RED II Directive, will in effect remove palm oil as a biofuel feedstock from the EU market. This is seen as discrimination in major ASEAN palm oil producing nations and caused bilateral relations to deteriorate further. Given existing jurisprudence, such differentiated treatment or selective exclusion of one crop would not comply with WTO law, exposing the EU to a time-consuming WTO dispute. Indonesia has already publicised its intent to bring the matter to the WTO, and Malaysia is expected to follow suit. However, retaliatory actions against European exports cannot be ruled out even before a WTO ruling is issued. A more positive assessment can be made of progress in tackling illegal, unreported and unregulated (IUU) fishing. Indonesia, Thailand, Vietnam and the Philippines are major fish producers: significant improvement in legislation and enforcement systems means IUU fishing can now be considered less likely to act as a brake on trade negotiations.
Keywords: 330